Hubungan prokrastinasi Akademik dengan Aktualisasi Diri Mahasiswa Fakultas Dakwah IAIN Purwokerto - Devi Alviana; Warto Warto (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
This article aims to find out whether there is a relationship of academic procrastination with self-actualization of activist student of Faculty of Da’wah IAIN Purwokerto. The method in this research is quantitative method. This type of research belongs to field research which is correlation by using quantitative approach. Respondents in this study amounted to 28 students who became administrators of intra organizations such as Student Senate, Student Executive Board, Student Association Department and Student Association of Study Programs at Faculty of Da’wah. Sampling technique with random sampling technique. In collecting the data the researchers used questionnaires. While the data analysis method used consisted of data collection, validity and reliability test, item analysis, correlation test, hypothesis test and conclusion. Result of research from method which have been done obtained by coefficient coefficient equal to 0,176 which show very weak correlation. Then test the hypothesis with n = 28, 5% significance in obtaining r table of 0.374 and shows the value of r arithmetic <r table so that it can be concluded that there is no significant relationship between academic procrastination and self-actualization student activist da’wah faculty.